PEDAGOGICAL FACILITIES AND INFORMATIONAL TECHNOLOGIES INTEGRATION PROVISION IN CONTEMPORARY EDUCATION (Scientific journal of the Fergana State University, 2023)
In this article, the integration of pedagogical and information technologies is a complex integrative process that includes the analysis and planning of the problem that covers all aspects of knowledge acquisition, the evaluation of the solution to the problem, the methods of organizing activities, and the integration of pedagogical and information technologies in improving the methodological preparation of future teachers, and through this, a potential pedagogue the content of upbringing, legal bases and existing conditions were studied.